Adverbia Penanda Aspek dalam Novel Rembulan Tenggelam di Wajahmu Karya Tere Liye - Wirna, Elfira Lusia; Juita, Novia (Persona: Kajian Bahasa dan Sastra, 2024)
This research was conducted to describe the use of the adverbs in the novel Rembulan Tenggelam di Wajahmu work Tere Liye. This type of research is descriptive qualitative linguisyic research. That is, this research aimd to describe th types and form of aspects of adverbial markers in the novel Rembulan Tenggelam di Wajahmu work Tere Liye. This reseach uses a descriptive metdod because the data collected is in the form sentences, not number. The data analysis technique in this research utilizes the Indonesian language corpus linguistic method using KORTARA to collect data and classify the amount of data. Data analysis technique are carried out by, (a) data reduction; (b) data presentation; (c) interesting conclusion. The research finds in the novel Rembulan Tenggelam di Wajahmu work Tere Liye adverbs aspect marker as many as 716 for the use of adverbs aspect markers. The conclusion of this research is the use of adverbs in novel Rembulan Tenggelam di Wajahmu work Tere Liye. The statement is evidenced by the phrase and sentence in the novel Rembulan Tenggelam di Wajahmu work Tere Liye which shows the appearance of adverbs of adverbs